The relationship between the itensity of common soil-transmitted intestinal helminthiasis and nutritional status. - Alojepan, Jake Lizada; Lee, Raymond Villasis
This study aimed to determine the relationship between intensity of infection of common soil-transmitted intestinal helminths (STH): Ascaris lumbricoides, Trichuris trichiura and Hookworm species (Ancylostoma duodenale and Necator americanus) and nutritional status among schoolchildren of Miag-ao West Central Elementary School (MWCES). This study also aimed to determined the prevalence of STH infection and nutritional status , either stunted or underweight schoolchildren. There were 285 study participants out of 436 schoolchildren of Miag-ao West Central Elementary School. Stool samples of the study participants were analyzed using Modified Kato-Katz Technique to determine the intensity of infections. The study participants were grouped according to the intensity of infection: negative, light and moderate to heavy. Nutritional status of the study participants was also determined and was classified into stunted, underweight and normal. Height-for-age value was used to determine stunting and weight-for-age value to determine those who are underwight. Frequency count was used for the descriptive analysis of the data gathered. The Chi-square test for association was used in the inferential statistics. The result of the study reveals that 51.2% of the respondents were infected with Ascaris lumbricoides, 36.5% with Trichuris trichiuria and 4.9% with hookworm. The findings also show that 16.8% of the respondents were stunted and 27.4% were underweight. Finally, study reveals that there is no significant relationship between the nutritional status and the intensity of infection of common soil transmitted intestinal helminths among schoolchildren of Miag-ao West Central Elementary School (p=0.706)